2012
DOI: 10.1002/14651858.cd006540.pub2
|View full text |Cite
|
Sign up to set email alerts
|

One-to-one dietary interventions undertaken in a dental setting to change dietary behaviour

Abstract: One-to-one dietary interventions undertaken in a dental setting to change dietary behaviour (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(73 citation statements)
references
References 77 publications
0
72
0
1
Order By: Relevance
“…The limitations of health education and lack of strong evidence for one-to-one dietary interventions in producing sustained behaviour change have been documented. 52,89 Owing to ethical and pragmatic constraints, the trial did not have an arm in which children received no intervention, so we cannot infer that preventative care provided in general dental practice is ineffective. Instead we compared the costs and effects of an enhanced prevention regime with a proxy for 'usual practice'.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The limitations of health education and lack of strong evidence for one-to-one dietary interventions in producing sustained behaviour change have been documented. 52,89 Owing to ethical and pragmatic constraints, the trial did not have an arm in which children received no intervention, so we cannot infer that preventative care provided in general dental practice is ineffective. Instead we compared the costs and effects of an enhanced prevention regime with a proxy for 'usual practice'.…”
Section: Resultsmentioning
confidence: 99%
“…Changing behaviour is notoriously difficult, 52,89 at least without a restriction of the availability of sugar in the environment. Legislative, regulatory and fiscal interventions have a stronger evidence base for changing behaviour than interventions applied to individuals.…”
Section: Implications For Policymentioning
confidence: 99%
“…The available evidence on the effects of dietary interventions in a dental setting has shown that there is limited or even no efficacy on caries experience, which is explained mainly by the lack of compliance (Harris et al 2012).…”
Section: Are Periodontal Diseases Related To Diet? If So What Are Thementioning
confidence: 99%
“…Previous studies have provided evidence that one-to-one dietary interventions in the dental setting can change the behavior of practitioners and patients [15]. The American Dietetic Association recommends collaboration between dietetics and dental professionals for oral health promotion and disease prevention and intervention [4].…”
Section: Introductionmentioning
confidence: 99%